How to tune and modify automotive engine management systems - Hartman, Jeff 1952- (Minneapolis, Minnesota Motorbooks, 2013)
"Understanding fuel injection and engine management systems is the key to extracting higher performance from today's automobiles in a safe, reliable, and driveable fashion. Turbochargers, superchargers, nitrous oxide, high compression ratios, radical camshafts: all are known to make horsepower, but without proper understanding and control of fuel injection and other electronic engine management systems, these popular power-adders will never live up to their potential and, at worst, can cause expensive engine damage. Drawing on a wealth of knowledge and experience and a background of more than 1,000 magazine articles on the subject, engine-control expert Jeff Hartman explains everything from the basics of fuel injection to the building of complex project cars. Hartman covers the latest developments in fuel-injection and engine management technology applied by both foreign and domestic manufacturers, including popular aftermarket systems. No other book in the market covers the subject of engine management systems from as many angles and as comprehensively as this book. Through his continuous magazine writing, author Jeff Hartman is always up-to-date with the newest fuel-injection and engine management products and systems."--
"How to Tune and Modify Engine Management Systems is Jeff Hartman's follow-up to his best-selling title of the same name. Featuring over 300 photographs and illustrations, this technical manual is a dream for those wishing to upgrade their stock engines."--
"First published in 2004 as How to tune and modify engine management systems"--Title page verso.
Includes index.
Keywords: Automobiles -- Motors -- Computer control systems; Automobiles -- Performance; Automobiles -- Motors -- Modification; TRANSPORTATION / Automotive / Repair & Maintenance; TECHNOLOGY & ENGINEERING / Automotive; TRANSPORTATION / Automotive / Customizing